ISOLASI DAN IDENTIFIKASI BAKTERI Vibrio sp DARI IKAN KERAPU SUNU (Plectropomus leopardus) - Ar. Syarif Hidayat (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2014)
This research about the isolation and identification Vibrio sp from sunu grouper fish (Plectropomus leopardus). This research aimed to observe the amount of vibrio bacteria species based on colony morphology and identificate morphological colony of vibrio isolated from grouper sunu fish (Plectropomus leopardus). Bacteria isolation was conducted by isolate some external organs (lesion on its body) and internal organ (jejenum) from grouper sunu fish (Plectropomus leopardus). Bacteria was grown on selective medium for vibrio, TCBS (Thiosulfate Citrate Bile Sucrose) agar. The incubation time was 24 hours at 30 C then the morphological colony was observed and biochemestry test was done. Morphology characteristic and biochemistry test result was matched with bacterial characteristic on Bargey’s Manual of Determinative Bacteriology. The result showed there are 3 isolate vibrio bacteria that was coded by V1, V2, V3. V1 morphological characteristis was rounded, edge is entire, convex elevation, green colony colour with blue in the center of colony and smooth tekstur. Based on biochemistry test V1 was indetificated as Vibrio parahaemolyticus. V2 morphological characteristic was rounded, edge is entire, tortous elevation, colony colour yellow and smooth tekstur. based on the biochemistry tes V2 was indentificated as Vibrio harveyi. Morphological characteristic of V3 was Irregular; egde is Undulate, elevation hill, colony colour yellow and own the smooth tekstur. Based on biochemistry test V3 was identificated as Vibrio alginolyticus.